2010
DOI: 10.1016/j.biocon.2009.11.030
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of fauna and flora species richness and abundance in plantations and pasture lands

Abstract: A meta-analysis of fauna and flora species richness and abundance in plantations and pasture lands. Biological conservation. Volume: 143Number: 3, pp 545-554. http://dx.doi.org/10.1016/j.biocon. 2009.11.030 Access to the published version may require journal subscription.Published with permission from: ELSEVIER We conducted a systematic global review of differences between timber plantations and pasture lands in terms of animal and plant species richness and abundance, and assessed the results using meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 65 publications
8
117
0
4
Order By: Relevance
“…Therefore, because of human-made activities on clear-cuts, the spruce reforestation severely restricted the shrub community development and obviously increased invasions by pioneer annuals and ruderals. Meanwhile, however, it was harmful to those remnant species populations sensitive to habitat alteration [3,12]. Thus we suggestthat to reduce the initial planting density of target trees during reforestation design was also a fundamental measure to decrease damage to initial ground vegetation and to allow the combination of reforestation and natural regeneration.…”
Section: Structure Of Tree Canopy Cover and Understory Vegetation Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, because of human-made activities on clear-cuts, the spruce reforestation severely restricted the shrub community development and obviously increased invasions by pioneer annuals and ruderals. Meanwhile, however, it was harmful to those remnant species populations sensitive to habitat alteration [3,12]. Thus we suggestthat to reduce the initial planting density of target trees during reforestation design was also a fundamental measure to decrease damage to initial ground vegetation and to allow the combination of reforestation and natural regeneration.…”
Section: Structure Of Tree Canopy Cover and Understory Vegetation Anmentioning
confidence: 99%
“…(2) How do the vascular plant groups (tree seedlings, shrubs, ferns, forbs, and graminoids) differ in species composition, richness, and community structure between the understory of the two forests? (3) What are the differences in structures of the overstory and understory and their relationships between the two forests? We hypothesized that: (H1) The naturally regenerated forests would host higher species diversity compared to the planted spruce forests, with woody plant diversity being the key driver of the diversity difference; and (H2) the tree canopy structure of the two forests disparately influences the structure and species diversity of the understory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the function of plantations has changed from being single purpose (i.e., timber production) to multipurpose (e.g., habitats for wild animals and plants), studies of plant species diversity [15,16] as well as ecosystem services and goods [17] provided by plantations have increased markedly (Table 1). In a meta-analysis of plant species richness in plantations compared to other land cover types (e.g., primary and secondary forest), Bremer and Farley [15] showed that plantations were more likely to contribute to biodiversity when established in degraded lands than when they replaced natural forest, grassland, and shrubland ecosystems.…”
Section: Studies On Plant Species Diversity and Species Richness In Pmentioning
confidence: 99%
“…Informed (and sometimes novel) management will be required to ensure that these areas play a useful conservation and ecosystem service roles. Furthermore, conservation outside reserves, including in plantations, is increasingly recognized as having a critical complementary role to traditional reserve-based conservation efforts (Lindenmayer and Franklin 2002;Felton et al 2010;Quine and Humphrey 2010).…”
Section: Tree Plantations As Novel Ecosystemsmentioning
confidence: 99%